Network Pharmacology and Molecular Docking to Elucidate the Potential Mechanism of Ligusticum Chuanxiong Against Osteoarthritis - Xiang, Cheng; Liao, Yilin; Chen, Zhuoyuan; Xiao, Bo; Zhao, Ziyue; Li, Aoyu; Xia, Yu; Wang, Pingxiao; Li, Hui; Xiao, Tao (Frontiers in Pharmacology, 2022)
Background: Osteoarthritis (OA) is a degenerative disease with serious effects on patients and Ligusticum chuanxiong (CX) has a certain curative effect on osteoarthritis in traditional Chinese medicine therapy. This study is based on network pharmacology and molecular docking technology to explore its potential mechanism. Methods: Components of Ligusticum chuanxiong treat osteoarthritis was screened in TCMSP database and targets was predicted by PharmMapper database, the osteoarthritis targets were collected in GeneCards database, the intersection genes were the possible targets of CX anti- OA. STRING database and Cytoscape software were utilized for protein-protein interaction analysis and further screening of core targets. Metascape database was used for the KEGG and GO enrichment analysis. Then, top 10 pathways were selected to construct "drug-compound-target-pathway-disease" network analysis. Finally, molecular docking was used to analyze the binding affinity of 7 compounds with core targets and TNF-α. Results: 7 compounds with 253 non repetitive targets of CX were screened from TCMSP database and 60 potential intersection targets of CX anti- OA were found. PPI network analysis showed that the core targets were ALB, AKT1, IGF1, CASP3, MAPK1, ANXA5, MAPK14, etc, while GO and KEGG pathway enrichment analysis showed that the relevant biological processes involved in the treatment of osteoarthritis by CX might include MAPK cascade and reactive oxygen species metabolic process, etc. The KEGG pathway analysis result was mainly associated with MAPK signaling pathway and PI3K-AKT signaling pathway etc. We further docked 7 ingredients with MAPK1 and MAPK14 enriched in MAPK pathway, and TNF-α as the typical inflammatory cytokine. The results also showed good binding affinity, especially FA, which maybe the most important component of CX anti-OA. Conclusion: Our research revealed the potential mechanism of CX in the treatment of OA, and our findings can also pave the way for the subsequent basic experimental verification and the research direction.